Electrochemical polymerase chain reaction using electroactive graphene oxide nanoparticles as detection labels - Ang, Wei Li (2021)
Electroactive nanocarbon tags are used in this work to label the DNA primers for the polymerase chain reaction (PCR) amplification of Cauliflower Mosaic Virus 35S promoter sequence, one of the most common markers for the detection of genetically modified organisms (GMOs). The PCR product carrying the electrochemical label can be directly detected on miniaturized electrodes, with the working signal being correlated to the reduction of oxygen-containing groups on the nanocarbon surface. A linear relationship was first established between the electrochemical signal and the nanomaterial concentration, both for the unconjugated electroactive nanocarbon and the conjugates with single-stranded and double-stranded DNA. After which, PCR amplification using a modified sense-primer was performed, and discrimination between amplified products from positive samples (GMO maize) and negative controls (non-GMO maize) was achieved successfully. After the optimization of PCR experimental conditions using the electroactive nanocarbon label, the electrochemical signal recorded as a function of PCR cycle number showed an exponential increase, very similar to that obtained in optical-based real-time PCR. From that, the extrapolated cycle threshold value showed a linear relationship with the initial number of copies of target DNA. Through the findings, electroactive nanocarbon material demonstrated high potential as electrochemical label for PCR, with the electrochemical signals produced directly correlated to the amount of PCR product. This work will serve as a stepping stone for the development of a robust, efficient, and portable electrochemical PCR system, with a reduced cost considering the wide availability and suitability of carbon nanomaterials for mass production, and the cost-effective electrochemical detection.